The changing agenda of Israeli sociology : theory, ideology, and identity - Ram, Uri (State University of New York Press, 1995)
Offers the first systematic and comprehensive overview of sociological thought in Israel, and pleads for a new agenda that would shift the focus from nation building to democratic and egalitarian citizenship formation.
Keywords: Sociology -- Israel.; Israel -- Politics and government.; Sociologie -- Israël.; Israël -- Politique et gouvernement.; SOCIAL SCIENCE -- Regional Studies.; SOCIAL SCIENCE -- Anthropology -- General.; Politics and government; Sociology; Israel; Sociologie.; Maatschappij.; Israël (staat)